Cultivation of three medicinal mushroom species on olive oil press cakes containing substrates - Andrej GREGORI; Franc POHLEVEN (Acta Agriculturae Slovenica)
Olive oil press cakes (OOPC) represent a waste that has a negative impact on environment. OOPC have little or no use and because of that solutions for their alternative use are sought after. In our experiments we investigated substrate mixtures composed of different proportions of OOPC, wheat bran, crushed corn seeds and beech sawdust for cultivation of Ganoderma lucidum, Lentinula edodes and Grifola frondosa fruiting bodies. The increasing amount of OOPC in fruiting bodies cultivation substrates resulted in decreasing production of fruiting bodies. Results show, that although OOPC in small portion can be successfully used as a medicinal mushroom fruiting bodies cultivating substrate, their use is rational only, if no other substrate composing materials can be found or when OOPC usage solves the problem of its deposition.